Sistem Pasca Westphalia, Interaksi Transnasional dan Paradiplomacy - Takdir Ali Mukti (Jurnal Hubungan Internasional, 2014)
Understanding world history will lead to understand world life today. World politics or international relations experiences many periodical momentums along the centuries, from barbarian to institutionalized system in Westphalia Treaty, with a lot of historical facts such as colonialism, world wars and cold war. The further period is from Westphalian system to post Westphalian system, where international societies have changed dramatically. This article will explore the new world system nowadays, and the responds of local actors in transnational relations.